# 2 perenthesis -2 perenthesis -3y equals 6?

2(-2)-3y=6 which is equal to -4 -3y = 6 which is equal to -3y = 10 which is equal to y = -(10 / 3) = -3.333...

### What is X plus 3y equals 2 and 2x - 3y equals 22?

Simple system. X + 3Y = 2 2X - 3Y = 22 ------------------------add 3X = 24 X = 8 --------------------now, insert back into one of the equations to find Y 8 + 3Y = 2 3Y = - 6 Y = - 2 ----------------check both equations 8 + 3(- 2) = 2 2 = 2 ---------------top checks 2(8) - 3(- 2) = 22 16 + 6 = 22 22 = 22 ----------------both are consistent, so…

### How do you solve 4x plus 3y equals 6 3x plus 3y equals 7?

given is that 4x+3y=6(3x+3y)=7 i.e., 6(3x+3y)=7 &&& 4x+3y=7 ---------------(1) 3x+3y=7/6 x+y=7/18 _________(2) multiply eqn(2) by 4 4x+4y=28/18 -------------------------(3) (3)-(1) 4x+3y-4x-4y=7-(28/18) y= -98/18 substitute y in eqn(2) x-98/18=7/18 x=7/18+98/18 x=105/18. therefore x=105/18 : y= -98/18

### What is the answer to 2x plus 4y equals -6 and x-3y equals 7 using substitution?

1) 2x + 4y = -6 2) x -3y = 7 We can add 3y to both sides of equation 2) to get x = 3y + 7 Now we can substitute 3y + 7 for x in equation 1). In other words, we replace any 'x'es in equation 1) with 3y + 7. 2x is two times x, so this becomes 2(3y + 7) which is two times 3y_and_seven Equation 1) becomes 2(3y +…